Fetal anemia: Diagnosis and management. (July 2019) - Prefumo, Federico; Fichera, Anna; Fratelli, Nicola; Sartori, Enrico
Abstract: Fetal anemia has been known for many years as a dangerous complication of pregnancy. Its most common causes are maternal alloimmunization and parvovirus B19 infection, although it can be associated with many different pathological conditions including fetal aneuploidies, vascular tumors, and arteriovenous malformations of the fetus or placenta and inherited conditions such as alpha-thalassemia or genetic metabolic disorders. Doppler ultrasonographic assessment of the peak velocity of systolic blood flow in the middle cerebral artery for the diagnosis of fetal anemia and intravascular intrauterine transfusion for its treatment are the current practice standards. Live birth rates as high as 95% have been reported in recent years. The additional role of intravenous immunoglobulin therapy and the long-term consequences of the condition are the subjects of active ongoing research. Highlights: The most common causes of fetal anemia are maternal alloimmunization and parvovirus B19 infection. Doppler of the peak velocity of systolic blood flow in the middle cerebral artery allows to diagnose fetal anemia. Intravascular intrauterine transfusion is the mainstay for treatment of fetal anemia. Survival rates as high as 95% have been reported in recent series.